IMPLEMENTASI PROGRAM KEWIRAUSAHAAN MELALUI PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI SMA NEGERI 2 BANGUNTAPAN BANTUL - Tugino Tugino; Enung Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study was to explore the process of implementing entrepreneurship programs through craft and entrepreneurship learning at SMA Negeri 2 Banguntapan Bantul. This research is a descriptive qualitative research. Data collection was carried out through interviews, observation, and document analysis. We conducted interviews with school principals, vice-principals, teachers, students, and parents. We conducted data analysis referring to the writing of Entrepreneurship Education (Naswan Suharsono, Undiksha), namely through steps to reduce data, present data, and draw conclusions. The results showed that 1) SMA Negeri 2 Banguntapan Bantul developed entrepreneurship programs that refer to the school's vision and mission; 2) Cultivating an entrepreneurial attitude is carried out in several stages of coordination, preparation and planning, entrepreneurship development in the curriculum, outreach to school members, motivation by practitioners and visits to DUDI, entrepreneurial IHT; 3) The implementation of entrepreneurship program development is carried out by integrating subjects and extracurricular activities; the formation of the Student Business Group (KUS), and the existence of the Bazaar.